2015
DOI: 10.1093/mnras/stv878
|View full text |Cite
|
Sign up to set email alerts
|

Outer and inner mass distributions of the irregular galaxies UGC 4284 and UGC 11861: constraining the baryonic content through stellar population synthesis studies

Abstract: In this article we investigate the outer and inner mass distributions of the irregular galaxies UGC 4284 and UGC 11861, taking advantage of published HI and Hα high resolution rotation curves and constraining the stellar disk of both galaxies throughout stellar population synthesis studies. In addition we take into account the gas content of both galaxies deriving the HI+He rotation curve. The deduced baryonic rotation curves (star+gas) are inadequate to account for the total mass of UGC 4284 and UGC 11861, fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 79 publications
(109 reference statements)
1
5
0
Order By: Relevance
“…We have to clarify that the values of the EIN form parameters, determined through our fitting analysis, are in total agreement with the outcomes of the Cold DM N-body numerical simulations of Navarro et al (2004), and Dutton & Macciò (2014) (DM14), given that, the EIN density profile, that those authors employ has the reciprocal shape index with respect to our profile, as also observed by Chemin et al (2011) (CH11). The STD λ index is also concordant with the prescription of STD, given that in the velocity formula derived in Repetto et al (2015), the STD index appear as the reciprocal of the STD index λ. We found different values of the indexes parameters of EIN and STD, for the Hα and HI RCs of UGC 8490 and UGC 9753, and a possible interpretation could be that the two distinct tracers denote different parts of the same gravitational potential, as partially confirmed by the fact that the resulting Hα and HI DM masses and scale radii delineate a dissimilar DM mass density distribution among the Hα and HI gaseous tracers.…”
Section: Fitting Strategy and Semi-axes Settingssupporting
confidence: 59%
See 1 more Smart Citation
“…We have to clarify that the values of the EIN form parameters, determined through our fitting analysis, are in total agreement with the outcomes of the Cold DM N-body numerical simulations of Navarro et al (2004), and Dutton & Macciò (2014) (DM14), given that, the EIN density profile, that those authors employ has the reciprocal shape index with respect to our profile, as also observed by Chemin et al (2011) (CH11). The STD λ index is also concordant with the prescription of STD, given that in the velocity formula derived in Repetto et al (2015), the STD index appear as the reciprocal of the STD index λ. We found different values of the indexes parameters of EIN and STD, for the Hα and HI RCs of UGC 8490 and UGC 9753, and a possible interpretation could be that the two distinct tracers denote different parts of the same gravitational potential, as partially confirmed by the fact that the resulting Hα and HI DM masses and scale radii delineate a dissimilar DM mass density distribution among the Hα and HI gaseous tracers.…”
Section: Fitting Strategy and Semi-axes Settingssupporting
confidence: 59%
“…the prescription of STD, given that in the velocity formula derived in Repetto et al (2015), the STD index appear as the reciprocal of the STD index λ. We found different values of the indexes parameters of EIN and STD, for the Hα and HI RCs of UGC 8490 and UGC 9753, and a possible interpretation could be that the two distinct tracers denote different parts of the same gravitational potential, as partially confirmed by the fact that the resulting Hα and HI DM masses and scale radii delineate a dissimilar DM mass density distribution among the Hα and HI gaseous tracers.…”
Section: Fitting Strategy and Semi-axes Settingsmentioning
confidence: 99%
“…This profile has already been used to model rotation curves for several galaxies (Karukes et al 2015;Repetto et al 2015) but not with a large sample. It can potentially solve the TBTF problem in the Local Group (Brook & Di Cintio 2015a) and explain the Tully-Fisher relation (Brook & Di Cintio 2015b).…”
Section: The Halo Response Due To Baryonic Processesmentioning
confidence: 99%
“…Martínez-García et al (2017) (MG17) have recently ideated an alternative method to that of ZB09 to avoid the production of spurious filamentary mass portions in the resultant mass maps of ZB09, and also to mitigate the creation of other possible mass artefacts originated by the apparent superposition of dust lanes and spiral arms in the sample of analysed galaxies. Some authors, that determined the mass distribution of galaxies through the analysis of the observed RCs, employed the SPS strategy to derive the mass and circular velocity curve of the stellar discs considered, the results obtained are diverse and dependent on the specific assumptions of the particular approach they adopted, but in general concordant with the first prescription described above Oh et al 2008;Kuzio de Naray et al 2008;Salucci et al 2008;de Denus-Baillargeon et al 2013) and also (Repetto et al 2015(Repetto et al , 2017 (the latter paper RP17).…”
Section: Introductionmentioning
confidence: 79%
“…The DM RCs fitting procedure is similar to the one applied in Repetto et al (2015) and RP17, the principal difference in this work is represented by the introduction of the prolate and oblate circular velocity fit. We employ the minuit fitting routine through the ROOT package (Brun & Rademakers 1997) to adjust the spherical, prolate and oblate circular velocity relations to the DM RCs of UGC 8490 and UGC 9753.…”
Section: Dm and Total Mass For Spherical Prolate And Oblate Geometriesmentioning
confidence: 99%